2020
DOI: 10.3390/met10030413
|View full text |Cite
|
Sign up to set email alerts
|

Rational Alloy Design of Niobium-Bearing HSLA Steels

Abstract: In the 61 years that niobium has been used in commercial steels, it has proven to be beneficial via several properties, such as strength and toughness. Over this time, numerous studies have been performed and papers published showing that both the strength and toughness can be improved with higher Nb additions. Earlier studies have verified this trend for steels containing up to about 0.04 wt.% Nb. Basic studies have shown that the addition of Nb increases the recrystallization-stop temperature, T5% or Tnr. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…It has been found that niobium alloy has more uniform and better mechanical properties. [14], [15]. The effect of rolling temperature on microstructure was investigated to see whether the material meets the DWTT specification.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that niobium alloy has more uniform and better mechanical properties. [14], [15]. The effect of rolling temperature on microstructure was investigated to see whether the material meets the DWTT specification.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce carbon emissions per unit of steel production or adopt alternative construction approaches [1], materials with a better strength-to-weight ratio have been introduced, with High-strength lowalloy (HSLA) steels standing out [2]. HSLA steels include minimal amounts of alloying elements (0.05-0.15% by weight), such as Mo, Nb, Ti, and V [3][4][5], and adding Nb to low-carbon steel can increase its strength by up to 50% [6,7] HSLA steels have a tensile strength greater than 450 MPa and their ductility can reach up to 30%. The improvement in the mechanical properties of HSLA steels is mainly due to the added microalloys, which provide grain refinement strengthening, dislocations, solid solution, and dispersion [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%